3D Scanner Using Infrared for Small Object - Marlindia Ike Sari; Anang Sularsa; Rini Handayani; Surya Badrudin Alamsyah; Siswandi Riki Rizaldi (JOIV : International Journal on Informatics Visualization, 2023)
Three-Dimensional scanning is a method to convert various distances set into object visualization in 3-dimensional form. Developing a 3D scanner has various methods and techniques depending on the 3d scanner's purpose and the size of the object target. This research aims to build a prototype of a 3D scanner scanning small objects with dimensions maximum(10x7x23)cm. The study applied an a-three dimensional(3D) scanner using infrared and a motor to move the infrared upward to get Z-ordinate. The infrared is used to scan an object and visualize the result based on distance measurement by infrared. At the same time, the motor for rotating objects gets the (X, Y) ordinates. The object was placed in the center of the scanner, and the maximum distance of the object from infrared was 20cm. The model uses infrared to measure the object's distance, collect the result for each object's height, and visualize it in the graphic user interface. In this research, we tested the scanner with the distance between the object and infrared were 7 cm, 10 cm, 15 cm, and 20 cm. The best result was 80% accurate, with the distance between the object and the infrared being 10cm. The best result was obtained when the scanner was used on a cylindrical object and an object made of a non-glossy material. The design of this study is not recommended for objects with edge points and metal material.